Prevalence and cesarean rates of immigrant adolescent pregnancies - Birge, Özer; Serin, Aliye Nigar; Kayar, İlkan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: aim of this study was to compare Syrian migrant adolescent pregnancies and Turkish adolescent pregnancies, who gave birth in Osmaniye State Hospital. Methods: 22,724 women who gave birth at the Osmaniye State Hospital obstetrics and gynecology department between January 2013 and January 2020 were screened retrospectively. 868 Turkish adolescent pregnant women and 522 Syrian migrant adolescent pregnant women were compared. Whether the differences between Turkish and Syrian adolescents were noteworthy (95% confidence interval) was determined using the independent samples t test and Pearson Chi-Square test with statistical software Minitab (version 16.0, USA). Results: A total of 22,724 births, including 15,883 Turkish and 6841 Syrian immigrants, were analyzed. The number of Turkish adolescent pregnant women was 868 (5.5%), the number of Syrian adolescent pregnant women was 522 (7.6%), the rate of Syrian adolescent pregnancy was higher. The cesarean rate was observed 36.7% in Turkish adolescent pregnancies and 20.1% in Syrian adolescent pregnants, cesarean rates were significantly higher in Turkish adolescent pregnants (p<0.001). When the total of 1390 (6.1%) adolescent pregnancies were evaluated in Osmaniye, where there were intense migrants and Syrian camp, the cesarean rate was found to be 30.5%, and the birth rate of low birth weight below 2500 gm was 11.1%. Conclusions: Maternal and fetal complications increase in adolescent pregnancies. War and migration are associated with poor obstetric outcomes in pregnancies. With Syrian immigration, an increase in adolescent pregnancy rate, cesarean rate, and low birth weight rate was observed in the region. For these reasons, studies should be done to prevent Syrian adolescent pregnancies. Social and education support, regular follow-up should be done to improve pregnancy outcomes. Adolescent pregnant women are more likely to have vaginal delivery. Therefore, normal vaginal delivery should be followed unless there is an emergency cesarean indication.